Analisis Perubahan Arsitektural Masjid Agung Kota Tegal - Mohamad Zuhdan Fanani Abdullah; Sahrul Aditia Putra (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
The Great Mosque of Tegal City is a historic building that has undergone numerous renovations since its establishment in 1825-1830. These renovations aimed not only to meet the functional and capacity needs of worshippers but also reflected modern architectural trends, occasionally compromising historical elements. This study employs a qualitative approach using documentation, observation, and literature synthesis methods to analyze the mosque's architectural changes. Using John Obert Voll's "continuity and change" theory, the research identifies the preserved original architectural elements and the modifications made. The findings reveal that while several original features, such as the mosque's core structure, remain intact, significant changes in renovations—such as the addition of floors, towers, and alterations to the gate design—have impacted the mosque's historical and aesthetic values. The study recommends the preservation of historical elements to maintain the mosque's cultural identity.